PELAKSANAAN HAK ANAK DIDIK PEMASYARAKATAN UNTUK MENDAPATKAN PENDIDIKAN DAN PENGAJARAN DIKAITKAN DENGAN WAJIB BELAJAR 9 TAHUN DI LEMBAGA PEMBINAAN KHUSUS ANAK (LPKA) PEKANBARU - Erick Van Lambok S. Sialagan; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Protege correctional supposed to get an education and teaching are the same as children in general is good and quality even though the child's status is prisoners. In this case the implementation of education and teaching in the Special Children's Development Institute (LPKA) Pekanbaru is not maximized. The research objective of this thesis, namely: First, the implementation of the rights of the students correctional to get an education and teaching associated with the compulsory nine years at the Institute for Development of Special Children (LPKA) Pekanbaru, Second, Obstacles encountered in the implementation of education and teaching, Third, efforts made in overcoming obstacles in the implementation of education and teaching.This type of research can be classified in this type of sociological juridical research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted at the Institute for Development of Special Children (LPKA) Pekanbaru, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data and data tertiary, technical data collectors in research this interview, questionnaire and literature study.From the research there are three main issues that can be inferred. First Instance, exercise of the right of education and instruction for inmates at Pekanbaru LPKA has been attempted as possible by interested parties. Shape the implementation of education and teaching given to students correctional just a hanky (Study Group) Package A, Package B, Package C and education skills in the form of courses sewing and weaving. Second, Obstacles encountered in the implementation of education and teaching is limited educators, inadequate infrastructure, lack of budget allocation and lack of cooperation with the relevant authorities. Third, efforts made in overcoming barriers to implementation of diversion, that the provision of sufficient and adequate educators, improve infrastructure, increase the budget allocation and maximize cooperation with the relevant authorities. Suggestions Author, First, the implementation of education and teaching should be carried out with maximum and must comply with the applicable curriculum at educational institutions are equal, Second, Party LPKA should provide a solution as soon as possible in order to fulfill the rights of the students correctional education and teaching can be received with a good, third, efforts made LPKA Pekanbaru to immediately be implemented.Keywords: Implementation - Rights - Learners Corrections - LPKA.